2013
DOI: 10.1097/ccm.0b013e318275cd75
|View full text |Cite
|
Sign up to set email alerts
|

How to Perform Indexing of Extravascular Lung Water

Abstract: Using either predicted or actual body weight for indexing extravascular lung water does not lead to independence of height, weight, and gender of the patient. Specifying a fixed range of normal or a uniform upper threshold for all patients is misleading for either method, despite widespread use. Our data suggest that indexing extravascular lung water to height is superior to weight-based methods. As we are not aware of any abnormal hemodynamic profile for brain tumor patients, we propose our findings to be a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…In one of the most recent studies [15], “Chew et al found that EVLW indexed to absolute body weight resulted in a stronger association with outcome” including mortality compared to EVLWI pred [24]. Despite the overall strong predictive capacity of EVLWI in this and other recent trials [12][19], these inconsistencies demonstrate the need to optimize indexation of EVLW. Therefore, we recently analyzed a prospectively maintained database regarding the association of EVLW to biometric data [18].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…In one of the most recent studies [15], “Chew et al found that EVLW indexed to absolute body weight resulted in a stronger association with outcome” including mortality compared to EVLWI pred [24]. Despite the overall strong predictive capacity of EVLWI in this and other recent trials [12][19], these inconsistencies demonstrate the need to optimize indexation of EVLW. Therefore, we recently analyzed a prospectively maintained database regarding the association of EVLW to biometric data [18].…”
Section: Introductionmentioning
confidence: 75%
“…This study demonstrated that height was the only biometric parameter independently associated to EVLW. These data were recently confirmed by Wolf et al, using a similar approach in a surgical group [19]. Despite these conclusive data, both studies did not investigate, if indexation of EVLW to height (EVLWI height ) provides better association to pulmonary function and outcome.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This improves accuracy in obese patients and improves correlation with severity of illness and survival in acute lung injury patients [105−107]. Recent data shows that no indexation at all or indexation related to height is better [108], as suggested by others [109,110]. The problem is that there are no good ranges for normal values and such algorithms and decision trees should be used with caution [21, 111].…”
Section: Step 8 Normal Values and Indexationmentioning
confidence: 99%
“…BW) and formulas (e.g. BSA) might improve indexation of volumetric parameters including GEDVI and extravascular lung water index (EVLWI) [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%